Clearance of Pseudomonas aeruginosa foreign-body biofilm infections through reduction of the cyclic di-GMP level in the bacteria - Chiang, Wen-Chi (2013)
Opportunistic pathogenic bacteria can engage in biofilm-based infections that evade immune responses and develop into chronic conditions. Because conventional antimicrobials cannot efficiently eradicate biofilms, there is an urgent need to develop alternative measures to combat biofilm infections. It has recently been established that the secondary messenger cyclic diguanosine monophosphate (c-di-GMP) functions as a positive regulator of biofilm formation in several different bacteria. In the present study we investigated whether manipulation of the c-di-GMP level in bacteria potentially can be used for biofilm control in vivo. We constructed a Pseudomonas aeruginosa strain in which a reduction in the c-di-GMP level can be achieved via induction of the Escherichia coli YhjH c-di-GMP phosphodiesterase. Initial experiments showed that induction of yhjH expression led to dispersal of the majority of the bacteria in in vitro-grown P. aeruginosa biofilms. Subsequently, we demonstrated that P. aeruginosa biofilms growing on silicone implants, located in the peritoneal cavity of mice, dispersed after induction of the YhjH protein. Bacteria accumulated temporarily in the spleen after induction of biofilm dispersal, but the mice tolerated the dispersed bacteria well. The present work provides proof of the concept that modulation of the c-di-GMP level in bacteria is a viable strategy for biofilm control.